Building the resilience of periurban communities to the impacts of climate change and urbanization. Issue 1 (23rd August 2020) - Narain, Vishal
Abstract : Purpose: This paper aims to describe how social capital is mobilized in the mediation of periurban water insecurity induced by urbanization and climate change. Investing in social capital through the process of creating mechanisms for civic engagement is an important means of building resilience of periurban communities. Design/methodology/approach: This paper draws on ethnographic and action research. The main sources of data were direct observation of water appropriation and access and semi-structured interviews. Convenience, snowball and theoretical sampling were used. Findings: The residents of periurban Gurgaon have lost access to water on account of urbanization and climate change. In this context, they mobilize social relationships to collectively improve their access to water. Norms of cooperation and kinship play an important role in the mediation of water insecurity. Creating social capital by building platforms for civic engagement helped to improve their water security. Originality/value: While there has been much interest in issues of periurban water insecurity, the role of social capital in the mediation of water insecurity has received scant attention. At the same time, while scholars have been interested in the role of social capital in adapting to the impacts of climate change, it has scarcely been studied in a periurban context. This paper seeks to bridge this research gap.